Adhesive organ regeneration in Macrostomum lignano. Issue 1 (December 2016) - Lengerer, Birgit; Hennebert, Elise; Flammang, Patrick; Salvenmoser, Willi; Ladurner, Peter
Abstract Background Flatworms possess pluripotent stem cells that can give rise to all cell types, which allows them to restore lost body parts after injury or amputation. This makes flatworms excellent model systems for studying regeneration. In this study, we present the adhesive organs of a marine flatworm as a simple model system for organ regeneration.Macrostomum lignano has approximately 130 adhesive organs at the ventral side of its tail plate. One adhesive organ consists of three interacting cells: one adhesive gland cell, one releasing gland cell, and one modified epidermal cell, called an anchor cell. However, no specific markers for these cell types were available to study the regeneration of adhesive organs. Results We tested 15 commercially available lectins for their ability to label adhesive organs and found one lectin (peanut agglutinin) to be specific to adhesive gland cells. We visualized the morphology of regenerating adhesive organs using lectin- and antibody staining as well as transmission electron microscopy. Our findings indicate that the two gland cells differentiate earlier than the connected anchor cells. Using EdU/lectin staining of partially amputated adhesive organs, we showed that their regeneration can proceed in two ways. First, adhesive gland cell bodies are able to survive partial amputation and reconnect with newly formed anchor cells. Second, adhesive gland cell bodies are cleared away, and the entire adhesive organ is build anew. Conclusion Our results provide the first insights into adhesive organ regeneration and describe ten new markers for differentiated cells and tissues inM. lignano . The position of adhesive organ cells within the blastema and their chronological differentiation have been shown for the first time.M. lignano can regenerate adhesive organsde novo but also replace individual anchor cells in an injured organ. Our findings contribute to a better understanding of organogenesis in flatworms and enable further molecular investigations of cell-fate decisions during regeneration.